Global policies for moving cities: the role of think tanks in the proliferation of Bus Rapid Transit systems in Latin America and worldwide (2020)
Implementation in the late nineties of Transmilenio, a Bus Rapid Transit (BRT) based transportation policy in Bogotá (Colombia), marked an inflection milestone for the replication processes of such urban transportation policies. Multiple actors and actions brought the Transmilenio model to numerous cities worldwide, first replicated in other Colombian and Latin American cities later it reached Turkey, China and India and then spread all over the world. This article explores the role of think tanks steering and promoting BRT policies during complexes processes and interactions of power among multiple scales. In doing so, the article situates itself within the research arenas studying linkages between local interests, demands and needs and the global neoliberal allocation of capital and expertise via consulting, advising commerce and construction activities. I argue that BRT promotion think tanks have emerged as powerful mechanisms mobilizing specific transportation policies acting as facilitators of movements via ‘policy translators’, promoters and network developers among the plethora of actors and interests. Methodology utilized is based on data from policy reports, archives and in-depth interviews exploring networked interactions while tracing linkages between think tanks and policy actors and observing knowledge dissemination arenas. This research contributes to the exploration of urban transportation epistemic communities and its role in urban change under a neoliberal global context and underlines the role of emerging policies from the south that permeate global policy arenas, traditionally dominated by actors from developed economies and discusses the mediation of global north institutions in the global south urban policy mobilities landscape. © 2020, © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor and Francis Group.